(untitled) (Mustansiria Dental Journal, 2019)
Fifteen human premolar teeth freshly extracted were used. Standardized class V was prepared on the buccal and palatal surfaces of each tooth, the teeth randomly divided into three groups according to the curing mode of composite resin: group I cured with quart-tungsten halogen, group II cured with Soft Start While group III cured with Plasma Arc. The increase in temperature internally (inside the pulp chamber) and externally (at the outer surfaces of the tooth) for each sample of the three groups was measured by using two K type thermocouple connected with electrical thermometer. Results: revealed a very high significant differences (P= 0.0001) among the three groups . Conclusion: Plasma Arc light curing unit showed significantly the highest increase in temperature, while the Soft Start gave lower value and Quartz Tungsten Halogen unit with lowest temperature rise internally and externally.